2011
DOI: 10.5653/cerm.2011.38.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Does blastomere biopsy in preimplantation genetic diagnosis affect early serum β-hCG levels?

Abstract: ObjectiveTo determine whether the serum β-human chorionic gonadotropin (hCG) profile following preimplantation genetic diagnosis (PGD) is lower than that of intracytoplasmic sperm injection (ICSI) cycles.MethodsA total of 129 PGD cycles and 1,161 age-matched ICSI cycles, which resulted in pregnancy (serum β-hCG≥5 mIU/mL) on post-ovulation day (POD) 12 were included. We compared the mean serum β-hCG levels on POD 12, 14, 21, and 28, doubling time of serum hCG, and created a cut-off value for predicting a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
1
12
1
Order By: Relevance
“…The differences in hCG-β levels among these studies could be explained by various factors including day of ET, embryo biopsy, method of fertilization, method of freezing and thawing, media of embryo culture and etiology of infertility, etc. [27,[35][36][37]. In our study, hCG-β levels were not affected by the embryonic age or the number of embryos transferred (data not shown).…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…The differences in hCG-β levels among these studies could be explained by various factors including day of ET, embryo biopsy, method of fertilization, method of freezing and thawing, media of embryo culture and etiology of infertility, etc. [27,[35][36][37]. In our study, hCG-β levels were not affected by the embryonic age or the number of embryos transferred (data not shown).…”
Section: Discussionsupporting
confidence: 42%
“…The cycles resulted in heterotopic pregnancies (both extrauterine and intrauterine pregnancy occur simultaneously, n = 3), or pregnancy losses after >20 weeks gestation (n = 35) were excluded. Pregnancies established with embryos with preimplantation genetic diagnosis (PGD) (n = 101) were also excluded, since PGD has been reported to affect hCG-β level [27]. Pregnancies with incomplete or missing POD 12 or 14 data (n = 664) or missing follow-up during pregnancy (n = 66) were excluded.…”
Section: Study Populationmentioning
confidence: 99%
“…Two groups have demonstrated initial lower β-hCG levels with pregnancies obtained after PGD compared with controls. 40,41 At the same time, the biochemical pregnancy rate, clinical miscarriage rate, and the take-home infant rate were similar in both groups. The lower β-hCG levels may result from the blastomere biopsy, which may decrease the β-hCGproducing activity of the trophoblast, especially at early pregnancy, or a delayed implantation that may occur in biopsied embryos.…”
Section: Is Pgd Safe? Embryo Development Pregnancy Rates and Childrmentioning
confidence: 71%
“…It has been previously demonstrated that in comparison to unbiopsied embryos, the serum ßhCG at the time of pregnancy test is lower in embryos biopsied at the cleavage stage . Furthermore, it has been demonstrated that the age of the woman at the time of the IVF cycle is negatively correlated to the initial serum ßhCG measurement, and that the initial serum ßhCG concentration is higher subsequent to a frozen embryo transfer in comparison to a fresh embryo transfer …”
Section: Discussionmentioning
confidence: 99%